Emotional and Behavioral Assessment of Youths With Visual Impairments Utilizing the BASC-2. (July 2021) - Sims, Stephanie Vetere; Celso, Brian; Lombardo, Ted
Introduction: Few studies have examined the psychological and mental health effects of visual impairments (i.e., blindness and low vision) on youths. Our objectives were to describe the behavioral and emotional profile of students with visual impairments, compare the BASC-2 composite scores for youths with visual impairments with the normative data to determine if significant differences exist, and compare the BASC-2 scores of students categorized as having low vision with students categorized as being totally blind.Methods: A total of 63 students with visual impairments entering a state school for the deaf and blind between 2012 and 2017 had a parent complete the BASC-2 Parent Rating Scale as part of the intake procedure. A retrospective study was conducted to determine patterns of emotional and behavioral strengths and weaknesses in students with low vision and blindness. A Multivariate Analysis of Covariance (MANCOVA) and Wilcoxon Rank Sums test were performed to test for differences between children who are blind and children with low vision.Results: Students with visual impairments showed higher levels of clinical symptoms such as anxiety and withdrawal. Statistically significant higher deficits were detected for the students with visual impairments on the Behavioral Symptoms Index and Internalizing Problems composites and significant lower differences for the Adaptive Skills and Externalizing Problems composites compared to the BASC-2 normative sample. When compared with youths with low vision, students who are blind had statistically significant scores (i.e., deficits) for adaptive skills and resiliency.Discussion: Our results suggest that a substantial proportion of students with visual impairments may experience more emotional and behavioral difficulties than the average youth while lacking the adaptive skills to manage their conduct adequately.Implications for practitioners: Professionals working with youths with visual impairments face a number of daunting challenges, since the conditions under the visually impaired umbrella are heterogeneous, and variation exists within a statistically low-incidence disability category. Therefore, those who work with youths with visual impairments have to apply various and unique methods to understand, train, teach, rehabilitate, or counsel these youths.